Pedagogy, Personality, and Proficiency: Disentangling the Effects of Character-Creativity Instruction and Instructor Qualifications on Student Achievement in Program Design Methodology - Darmojo, Hardjito S.; Siswosuharjo, Partono; Rossa, M Adila; Al-Bahra; Qohar, Abdul (Journal La Edusci, 2026)
This research advances a more integrative model of programming education. It challenges the enduring myth that programming is solely a “hard skill” domain governed by innate logic, and instead positions it as a socio-cognitive-ethical practice shaped by how and by whom it is taught. This study employs a quasi-experimental, non-equivalent control group design with pretest–posttest measurements to examine the independent and interactive effects of two key predictors Character-Creativity Instruction (CCI) and instructor qualifications on student achievement in a foundational Program Design Methodology course. The finding that mathematical-logical ability explains only 22.3% of variance in programming achievement; Our moderation analysis reveals a crucial insight: pedagogical innovation is not self-actualizing. CCI’s efficacy is contingent upon the instructor’s capacity to enact it meaningfully; The large effect sizes observed in higher-order competencies such as algorithmic design and problem decomposition challenge the artificial dichotomy between “hard” technical skills and “soft” human attributes; Practically, our findings advocate for a dual investment strategy that is curriculum reform and Faculty development. The conclusion is these findings dismantle the persistent “math myth” in computing education and reframe programming as a socio-cognitive-ethical practice where character, creativity, and teaching quality are not peripheral “soft skills,” but core determinants of technical mastery